Embracing virtual support: A phenomenological study on the lived experiences of Filipino guidance counselees during the Covid-19 pandemic - Anna Patricia B. Agoncillo (Universitas Airlangga, 2023)
The Covid-19 pandemic profoundly impacted student and faculty well-being, necessitating a closer examination of guidance counselee experiences in virtual counseling. This research aims to address the unique challenges and benefits of virtual counseling during crises and improve guidance counseling delivery. This qualitative research explored the experiences and challenges of Filipino guidance counselees during virtual counseling amid the pandemic using phenomenological inquiry. Ten purposively selected participants underwent in-depth interviews, then the information was transcribed and analyzed thematically. Analysis revealed three major themes: Psychological struggles, challenges of virtual counseling, and the importance of virtual counseling. Participants discussed psychological struggles, pre-existing mental health conditions, and challenges like poor Internet connectivity. They emphasized the significance of virtual counseling for well-being. The findings underscore recognizing and addressing counselees' psychological struggles during the pandemic. Effective support must mitigate challenges like technological literacy and resource constraints. Virtual counseling maintains connections despite social distancing restrictions. This research provides valuable insights into guidance counselee experiences during the Covid-19 pandemic in the Philippines. It emphasizes embracing virtual counseling advantages while addressing specific challenges. Policymakers and school leaders should recognize counselor expertise and provide comprehensive support. Further research is recommended to develop interventions for different age groups and educational levels. Understanding and supporting guidance counselees to promote mental health and overall development.